9 - Children’s Experiences of Support Received from Men in Rural KwaZulu-Natal - Makusha, Tawanda; Richter, Linda; Bhana, Deevia (Africa Development, 2021)
Studies of fathers’ involvement in their children’s are usually based on men’s self-reports, women’s appraisals or children’s accounts of men’s involvement. This paper explores men’s support of children aged 9-10 years living in rural KwaZulu-Natal, as reported by children, women and men. In-depth interviews were conducted with twenty focal children, twenty female caregivers and sixteen fathers/father-figures nominated by the children in twenty randomly selected households. We find that men are important in children’s lives. The nomination of a father-figure by all children, even if the man was not their biological father, ascertained that all children receive some support from men. Our data highlight the influence of biological ties, co-residence, family social network, and marriage or father-mother relationship on fathers’ involvement with their children – financial and the quality of their interaction. This study improves methodologies and addresses the validity, reliability and interrelations of children, men and women’s reports of men’s involvement in providing support to children in a South African context. We were able to determine the informal, local systems of family support and the variety of contributions made by men in supporting children. In this way, the study provide a basis for research on local father involvement and for future comparison.